2004
DOI: 10.1051/0004-6361:20047035
|View full text |Cite
|
Sign up to set email alerts
|

Wind clumping and the wind-wind collision zone in the Wolf-Rayet binaryγ2 Velorum

Abstract: Abstract. We present XMM-Newton observations of γ 2 Velorum (WR 11, WC8+O7.5III, P = 78.53 d), a nearby Wolf-Rayet binary system, at its X-ray high and low states. At high state, emission from a hot collisional plasma dominates from about 1 to 8 keV. At low state, photons between 1 and 4 keV are absorbed. The hot plasma is identified with the shock zone between the winds of the primary Wolf-Rayet star and the secondary O giant. The absorption at low state is interpreted as photoelectric absorption in the Wolf-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
82
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(96 citation statements)
references
References 54 publications
14
82
0
Order By: Relevance
“…At this particular phase, the line of sight to the observer essentially goes through the O wind and unveils the X-ray emitting wind interaction zone that is much more absorbed at other phases due to the intervening dense WR wind. This result has been confirmed and further refined by more recent observations and models (Schild et al 2004;Henley et al 2005).…”
Section: Introductionsupporting
confidence: 79%
“…At this particular phase, the line of sight to the observer essentially goes through the O wind and unveils the X-ray emitting wind interaction zone that is much more absorbed at other phases due to the intervening dense WR wind. This result has been confirmed and further refined by more recent observations and models (Schild et al 2004;Henley et al 2005).…”
Section: Introductionsupporting
confidence: 79%
“…While X-ray variability as a function of orbital phase has been observed in WR11 (e.g. Schild et al 2004) that system is observed at higher inclination, such that significant orbital variation in the wind properties and hence line of sight extinction are present, which would be absent for the putative low inclination configuration proposed here. Consequently, one can at least qualitatively understand the X-ray properties of W239, although quantitative confirmation would require a tailored hydrodynamical simulation, which currently appears unwarranted given the lack of observational constraints.…”
Section: The Nature Of the W239 Systemmentioning
confidence: 49%
“…Indeed, practical examples of this multicolumn behaviour have been reported on several occasions, e.g. in γ 2 Vel (Schild et al 2004) but also in another context in γ Cas (Smith et al 2004). …”
Section: Notesmentioning
confidence: 85%
“…An additional possible X-ray source is present in the massive binary systems where the winds of the two components are colliding (Stevens et al 1992). This phenomenon is also present in WR+O binaries (see for WC+O, γ 2 Vel, Willis et al 1995;Stevens et al 1996;Schild et al 2004;WR 140, Pollock et al 2005;Zhekov & Skinner 2000;and for WN+O, V444 Cyg, Maeda et al 1999;WR 22, Gosset et al 2009;WR 25, Pollock & Corcoran 2006;Gosset 2007 andFig. 29 of Güdel &Nazé 2009;WR147, Pittard et al 2002;Zhekov & Park 2010).…”
Section: Introductionmentioning
confidence: 85%